Book Review: Ancient Egyptian Imperialism. By Ellen Morris. Pp. 320. Hoboken, NJ: Wiley-Blackwell, 2018. ISBN 978-1-405-13678-5. Price £24. - Flammini, Roxana (2021)
Fil: Flammini, Roxana. Pontificia Universidad Católica Argentina; Argentina